Validation of laser doppler flowmetry to measure dermal blood flow of the pinnae in dogs with pinnal alopecia. Issue 1 (13th October 2022) - Ide, Kaori; Tokunaga, Makoto; Hiratsuka, Shogo; Iwasaki, Toshiroh; Nishifuji, Koji
Abstract: Background: Laser Doppler flowmetry (LDF) is a noninvasive method of measuring regional blood flow in humans. However, this method has not been widely applied to measure blood flow in dogs. Hypothesis/Objectives: We hypothesised that LDF can measure changes in blood flow in canine pinnae accurately. The objectives were to determine whether LDF could accurately detect dermal blood flow changes in canine pinnae caused by haemodynamic drugs and characterize the dermal blood flow in dogs with pinnal alopecia. Animals: Sixteen laboratory‐owned healthy dogs, 25 client‐owned healthy control dogs and six dogs with pinnal alopecia suspected to be secondary to ischaemic dermatoses. Materials and Methods: Clinical doses of the haemodynamic drugs atropine, medetomidine and dibutyryl cyclic adenosine monophosphate (dBcAMP), as well as topical dBcAMP, were administered to healthy beagles. Subsequently, an LDF apparatus was attached to the pinnae to analyse changes in dermal blood flow. Finally, LDF was used to measure auricular dermal blood flow in dogs with pinnal alopecia compared to healthy dogs. Results: Dermal blood flow increased after atropine injection, during dBcAMP infusion and after topical dBcAMP ointment application, and decreased after medetomidine injection. Auricular dermal blood flow (in mL/min/100 g tissue) was significantly ( p  < 0.05) lower in dogs with pinnal alopecia than in healthy dogs. Conclusions and Clinical Relevance: Laser Doppler flowmetry is useful for measuring dermal blood flow in canine pinnae; it can be a noninvasive method to monitor ischaemic conditions of dog skin. Abstract : Background – Laser Doppler flowmetry (LDF) is a noninvasive method of measuring regional blood flow in humans. However, this method has not been widely applied to measure blood flow in dogs. Hypothesis/Objectives – We hypothesised that LDF can measure changes in blood flow in canine pinnae accurately. The objectives were to determine whether LDF could accurately detect dermal blood flow changes in canine pinnae caused by haemodynamic drugs and characterize the dermal blood flow in dogs with pinnal alopecia. Conclusions and clinical importance – Laser Doppler flowmetry is useful for measuring dermal blood flow in canine pinnae; it can be a noninvasive method to monitor ischaemic conditions of dog skin. Résumé: Contexte: Le LDF (Laser Doppler flowmetry) est une méthode non invasive de mesure du débit sanguin régional chez l'homme. Cependant, cette méthode n'a pas été largement appliquée pour mesurer le flux sanguin chez les chiens. Hypothèse/Objectifs: Nous avons émis l'hypothèse que le LDF peut mesurer avec précision les changements du flux sanguin dans les pavillons de chien. Les objectifs étaient de déterminer si LDF pouvait détecter avec précision les modifications du flux sanguin dermique dans les pavillons auriculaires de chien causées par des médicaments hémodynamiques et caractériser le flux sanguin dermique chez les chiens atteints d'alopécie auriculaire. Animaux: Seize chiens sains appartenant au laboratoire, 25 chiens témoins sains appartenant à des clients et six chiens atteints d'alopécie auriculaire suspectée d'être secondaire à des dermatoses ischémiques. Matériels et méthodes: Des doses cliniques des médicaments hémodynamiques atropine, médétomidine et dibutyryl adénosine monophosphate cyclique (dBcAMP), ainsi que du dBcAMP topique, ont été administrées à des beagles sains. Par la suite, un appareil LDF a été attaché aux pavillons pour analyser les changements dans le flux sanguin dermique. Enfin, le LDF a été utilisé pour mesurer le débit sanguin dermique auriculaire chez les chiens atteints d'alopécie pinnale par rapport aux chiens en bonne santé. Résultats: Le débit sanguin dermique a augmenté après l'injection d'atropine, pendant la perfusion de dBcAMP et après l'application topique de pommade dBcAMP, et a diminué après l'injection de médétomidine. Le débit sanguin dermique auriculaire était significativement plus faible chez les chiens atteints d'alopécie pinnale que chez les chiens en bonne santé. Conclusions et importance clinique: La flumétrie laser Doppler est utile pour mesurer le débit sanguin dermique dans les oreilles de chiens; il peut s'agir d'une méthode non invasive pour surveiller les conditions ischémiques de la peau du chien. Resumen: Introducción: La flujometría láser Doppler (LDF) es un método no invasivo para medir el flujo sanguíneo regional en humanos. Sin embargo, este método no se ha aplicado ampliamente para medir el flujo sanguíneo en perros. Hipótesis/Objetivos: Planteamos la hipótesis de que LDF puede medir con precisión los cambios en el flujo sanguíneo en las orejas caninas. Los objetivos eran determinar si LDF podía detectar con precisión cambios en el flujo sanguíneo dérmico en pinnas caninas causados por fármacos hemodinámicos y caracterizar el flujo sanguíneo dérmico en perros con alopecia pinnal. Animales: Dieciséis perros sanos de laboratorio, 25 perros de control sanos de clientes y seis perros con alopecia pinnal sospechosa de ser secundaria a dermatosis isquémica. Materiales y métodos: Se administraron dosis clínicas de los fármacos hemodinámicos atropina, medetomidina y monofosfato de adenosina cíclico de dibutirilo (dBcAMP), así como dBcAMP tópico, a sabuesos sanos. Posteriormente, se adjuntó un aparato LDF a los pabellones auriculares para analizar los cambios en el flujo sanguíneo dérmico. Finalmente, se usó LDF para medir el flujo sanguíneo dérmico auricular en perros con alopecia pinnal en comparación con perros sanos. Resultados: El flujo sanguíneo dérmico aumentó después de la inyección de atropina, durante la infusión de dBcAMP y después de la aplicación tópica de pomada de dBcAMP, y disminuyó después de la inyección de medetomidina. El flujo sanguíneo dérmico auricular fue significativamente menor en perros con alopecia pinnal que en perros sanos. Conclusiones e importancia clínica: La flujometría láser Doppler es útil para medir el flujo sanguíneo dérmico en pabellones auriculares caninos; puede ser un método no invasivo para monitorizar las condiciones isquémicas de la piel del perro. Zusammenfassung: Hintergrund: Die Laser Doppler Flowmetrie (LDF) ist eine nicht invasive Methode regionale Blutflüsse beim Menschen zu messen. Diese Methode wurde jedoch bisher nicht weitläufig angewendet, um den Blutfluss bei Hunden zu messen. Hypothese/Ziele: Wir hypothetisierten, dass die LDF Veränderungen im Blutfluss in der Pinna von Hunden genau messen kann. Die Ziele waren, festzustellen, ob LDF die Änderungen des dermalen Blutflusses, der durch hämodynamische Medikamente verursacht wird, in der Pinna des Hundes genau bestimmen kann. Außerdem sollte der dermale Blutfluss bei Hunden mit Ohrrand Alopezie charakterisiert werden. Tiere: Sechzehn gesunde Labor‐Hunde, 25 Hunde in Privatbesitz als gesunde Kontrollhunde, und sechzehn Hunde mit einer Alopezie des Ohrrandes, die sekundär, vermutlich aufgrund ischämischer Dermatosen, entstanden ist. Materialien und Methoden: Klinische Dosen des hämodynamischen Wirkstoffs Atropin, Medetomidin und Dibutyryl Cyclic Adenosin Monophosphat (dBcAMP), sowie topisches dBcAMP wurden gesunden Beagles verabreicht. In der Folge wurde ein LDF Apparat an die Pinnae angehängt, um Veränderungen des dermalen Blutflusses bei gesunden Hunden zu vergleichen. Ergebnisse: Der dermale Blutfluss nahm nach der Atropininjektion, während dBcAMP Infusion und nach topischer dBcAMP Salbenapplikation zu, jedoch nach Medetomidin Injektion ab. Der aurikuläre dermale Blutfluss war bei Hunden mit einer Alopezie des Ohrrandes signifikant niedriger als bei gesunden Hunden. Schlussfolgerungen und klinische Bedeutung: Laser Doppler Flowmetrie ist eine nützliche Methode, um den dermalen Blutfluss in der Pinna des Hundes zu messen; es handelt sich dabei um eine nichtinvasive Methode, um ischämische Zustände in der Hundehaut zu überwachen. 要約: 背景: レーザードップラー流速計(LDF)は、ヒトの局所血流を測定する非侵襲的な方法である。しかし、イヌの血流測定にはあまり応用されていない。 仮説・目的: 我々は、LDFがイヌの耳介における血流の変化を正確に測定することができると仮定した。その目的は、LDFが血行力学的薬剤によるイヌの耳介の皮膚血流変化を正確に検出できるかどうか、また耳介脱毛のイヌの真皮血流を特徴づけることであった。 供試動物: 実験室所有の健常犬16頭、オーナー所有の健常犬25頭、虚血性皮膚疾患に続発すると疑われる耳介脱毛症のイヌ6頭を対象とした。 材料と方法: 健常ビーグル犬に臨床用量の血行動態薬であるアトロピン、メデトミジン、ジブチリル環状アデノシン一リン酸(dBcAMP)、および外用dBcAMPを投与した。その後、LDF装置を耳介に装着し、皮膚血流の変化を解析した。最後に、LDFを用いて耳介真皮血流を測定し、健常犬と耳介脱毛犬を比較した。 結果: 真皮血流は、アトロピン注射後、dBcAMP注入中、dBcAMP軟膏外用後に増加し、メデトミジン注射後に減少した。耳介真皮血流は、健常犬に比べ耳介脱毛犬で有意に低下した。 結論と臨床的重要性: レーザードップラー血流計は犬の耳介真皮血流測定に有用であり、犬の皮膚の虚血状態をモニターする非侵襲的な方法となりうる。 摘要: 背景: 激光多普勒血流仪 (LDF) 是一种测量人体局部血流的无创方法。但该方法尚未广泛应用于测量犬的血流量。 假设/目的: 我们假设 LDF 可以准确测量犬耳廓的血流变化。目的是确定 LDF 是否可准确检测血液动力学药物引起的犬耳廓皮肤血流量变化，并表征耳廓脱毛犬的皮肤血流量。 动物: 16只实验室拥有的健康犬、25只客户拥有的健康对照犬和6只疑似继发于缺血性皮肤病的耳廓脱毛犬。 材料和方法: 对健康比格犬给予临床剂量的血液动力学药物阿托品、美托咪定和二丁酰环磷酸腺苷 (dBcAMP)，以及局部dBcAMP。随后，将 LDF 装置连接到耳廓，以分析皮肤血流量的变化。最后，使用 LDF 测量与健康犬相比，耳廓脱毛犬的耳廓真皮血流量。 结果: 阿托品注射后、dBcAMP输注时及外用 dBcAMP 软膏后皮肤血流量增加，美托咪定注射后皮肤血流量减少。耳廓脱毛犬耳廓真皮血流量明显低于健康犬。 结论和临床重要性: 激光多普勒血流测定法可用于测量犬耳廓的皮肤血流量；其可作为监测犬皮肤缺血状况的非侵入性方法。 Resumo: Contexto: A fluxometria laser doppler (FLD) é um método não invasivo de mensuração do fluxo sanguíneo regional em humanos. Entretanto, este método ainda não foi amplamente aplicado para mensurar o fluxo sanguíneo em cães. Hipótese/Objetivos: Nós supomos que FLD poderia mensurar as alterações no fluxo sanguíneo no pavilhão auricular de cães com precisão. Os objetivos foram determinar se FLD pode detectar alterações no fluxo sanguíneo dérmico na orelha canina causados por fármacos hemodinâmicos e caracterizar o fluxo sanguíneo dérmico em cães com alopécia no pavilhão auricular. Animais: Dezesseis cães saudáveis de laboratório, 25 cães de cliente saudáveis e seis cães com alopecia do pavilhão auricular supostamente secundária a dermatoses isquêmicas. Materiais e métodos: Doses clínicas dos fármacos hemodinâmicos atropina, medetomidina e adenosina monofosfato cíclico dibutiril (dBcAMP), bem como dBcAMP tópico, foram administrados a beagles saudáveis. Subsequencialmente, um aparato FLD foi instalado no pavilhão auricular para analisar as alterações no fluxo sanguíneo dérmico. Finalmente, FLD foi utilizada para mensurar o fluxo sanguíneo dérmico em cães com alopecia de pavilhão auricular, comparado aos cães normais. Resultados: O fluxo sanguíneo dérmico foi aumentado após a injeção de atropina, durante infusão de dBcAMP, e após aplicação de dBcAMP tópico, e reduzido após injeção de medetomidina. O fluxo sanguíneo dérmico auricular foi significativamente menor em cães com alopecia de pavilhão auricular que em cães saudáveis. Conclusões e importância clínica: A fluxometria laser doppler é útil para a mensuração do fluxo sanguíneo dérmico na orelha canina; pode ser um método não invasivo de monitorar condições isquêmicas na pele canina.